1987
DOI: 10.1017/s0022215100103391
|View full text |Cite
|
Sign up to set email alerts
|

The role of intranasal splints in the prevention of post-operation nasal adhesions

Abstract: IntroductionIntranasal splints, which are widely used following nasal surgery, were first described by Salinger and Cohen in 1955. While the first splints were fashioned from any suitable material such as strips of X-ray film or even the polythene tops of coffee cans (Wright, 1969), a variety of preformed splints are now available including ingenious devices which maintain pressure on the septum by using inbuilt magnets (Goode, 1982). Splints were initially introduced to support the reconstructed septum, but s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 4 publications
0
21
1
Order By: Relevance
“…Septal suture is recommended as an alternative to packing. There are literatures reports that septal sutures is better in terms of postoperative pain and complications and that there is no need to use splints (2,9,10,13,14,(20)(21)(22)(23). Some of these studies have been conducted before the 2000s; today, thin, flexible, integral airway, and comfortable silicone splints are used.…”
Section: Discussionmentioning
confidence: 99%
“…Septal suture is recommended as an alternative to packing. There are literatures reports that septal sutures is better in terms of postoperative pain and complications and that there is no need to use splints (2,9,10,13,14,(20)(21)(22)(23). Some of these studies have been conducted before the 2000s; today, thin, flexible, integral airway, and comfortable silicone splints are used.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the complications associated with nasal packing subjecting patients randomized to the septal surgery‐only arm to packing in the absence of proven benefit would be unethical. 5 On the other hand leaving the patients randomized to turbinectomy without nasal packing or splints in the knowledge of the advisability of these precautions to reduce complications, 11,13 would also be unethical. The scientific validity of the study would have been improved if these constraints did not exist.…”
Section: Discussionmentioning
confidence: 99%
“… 24 The role of silastic sheets in obtaining these effects has been debated. While Campbell et al 25 reported that a silastic splint was effective in preventing intranasal adhesion, Cook et al 26 reported no clear advantage. In a randomized double-blinded controlled trial by Jung et al, 27 a silastic splint revealed a significant positive effective in preventing postoperative adhesion after septoplasty.…”
Section: Discussionmentioning
confidence: 99%